ANALYSIS ABILITIES OF STUDENTS ABOUT ISLAMIC LAW MATERIALS IN THE CONTEXT OF DAILY LIFE - Suhartini, Andewi; Nursobah, Asep; Basri, Hasan; Ruswandi, Uus (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2023)
Abstract: Learning fiqh should be able to strengthen students' beliefs about the moderation of Islamic law. As a scientific discipline, fiqh discusses syara law based on how it is formulated and implemented in everyday life. This study aims to reveal the ability of Senior High School (SMA) students in analyzing the moderation of Islamic law that they learn in accordance with the 2013 curriculum in the subject of Islamic Religious Education and Character, which includes the law of janazah review, and the law of khutbah, tablig and da'wah by linking it to the context of everyday life. This study used a survey method, with tests as a data collection tool conducted at SMANs in Semarang, Bogor and Makassar in the even semester of the 2019/2020 school year. The results showed that by thinking at a high level at the level of analysis, students could find the moderate values ​​of Islamic law in the context of everyday life. Abstrak: Pembelajaran fiqih semestinya dapat memperkuat keyakinan peserta didik tentang kemoderatan hukum Islam. Sebagai disiplin ilmu, fiqih membahas hukum syara berdasarkan cara perumusan dan implementasinya dalam kehidupan sehari-hari. Penelitian ini bertujuan mengungkap kemampuan peserta didik Sekolah Menengah Atas (SMA) dalam menganalisis kemoderatan hukum Islam yang dipelajarinya sesuai dengan kurikulum 2013 pada mata pelajaran Pendidikan Agama Islam dan Budi Pekerti, yang meliputi hukum pemulasaraan Janazah, hukum khutbah, tablig dan dakwah dengan mengaitkannya kepada konteks kehidupan sehari-hari. Penelitian ini menggunakan metode survei, dengan tes sebagai alat pengumpul data yang dilakukan di SMAN di Semarang, Bogor, dan Makassar pada semester genap tahun ajaran 2019/2020. Hasil penelitian menunjukkan bahwa dengan berpikir tingkat tinggi pada tingkat analisis, peserta didik dapat menemukan nilai-nilai kemoderatan hukum Islam dalam konteks kehidupan sehari-hari.